Effects of land use on catchment runoff and soil loss in the sub-humid Ethiopian highlands - Dagnew, D.C.; Guzmán, Christian D.; Akal, Adugnaw T.; Tebebu, T.Y.; Zegeye, Assefa D.; Mekuria, Wolde; Tilahun, Seifu A.; Steenhuis, Tammo S. (Elsevier, 2017)
Land use and management affects runoff and soil loss from a catchment. The present study investigated the effects of land use on runoff and suspended sediment concentration and yield in the northwestern Ethiopia. We selected two small catchments: cultivated land and grassland dominated catchments within the 95 ha Debre Mawi catchment. Hydrometric and sediment concentration data were collected for five years (i.e., 2010–2014). Significant (p < 0.05) differences in daily, monthly and annual runoff, as well as suspended sediment concentrations were observed between cultivated land and grassland dominated catchments. The greater runoff, suspended sediment concentration and yield in the cultivated catchment could be attributed to repeated tillage and low soil organic matter. Repeated tillage in the cultivated land lead to soil disturbance and the low organic matter lead to aggregate instability, both of which consequently increase the detachment of soil particles and transport by generated runoff. Our results support that land management practices that involve lower soil disturbance and increase ground cover on degraded highland areas such as the Ethiopian highlands could help reduce runoff and soil loss.